Performance evaluation of PI and PI-fuzzy logic controller FPGA based permanent magnet synchronous motor drive - Murmu, Rajendra; Kumar Singh, Arvind (International Journal of Engineering and Technology, 2020)
This paper depicts an experimental validation and simulation for speed control under load and no load conditions. It delineates the detail study of a closed loop vector controlled permanent magnet synchronous motor drive. This system consists of two loops for smooth speed tracking as well as reduced torque undulation. PMSM drives facilitate better dynamic responses during both steady state and dynamic conditions by monitoring the component of torque current. The resistive loads are varied and resultant speed and torque are studied. Experimental work has been performed on PMSM drives under different conditions and results are compared with conventional PI and Fuzzy logic controller.Â Â